The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1523/jneurosci.1981-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Structural Change of GABAA Receptor-Associated Protein Underlies Long-Term Potentiation at Inhibitory Synapses on a Cerebellar Purkinje Neuron

Abstract: Fast inhibitory synaptic transmission is predominantly mediated by GABA A receptor (GABA A R) in the CNS. Although several types of neuronal activity-dependent plasticity at GABAergic synapses have been reported, the detailed mechanism is elusive. Here we show that binding of structurally altered GABA A R-associated protein (GABARAP) to GABA A R ␥2 subunit and to tubulin is critical for long-term potentiation [called rebound potentiation (RP)] at inhibitory synapses on a cerebellar Purkinje neuron (PN). Either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 50 publications
(74 reference statements)
2
71
0
Order By: Relevance
“…Although a scrambled control peptide had no effect on the NMDA-mediated increase in GABA A R surface expression (48.9 Ϯ 9.18% increase from control; n ϭ 5; p Ͻ 0.05), when cells were pretreated with the GABARAP inhibitory peptide for 30 min, NMDA induced a significant decrease in GABA A R surface levels (Ϫ38.17 Ϯ 5.15%; n ϭ 5; p Ͻ 0.05). As reported previously (Kawaguchi and Hirano, 2007), disruption of the GABARAP-GABA A R interaction with the GABARAP inhibitory peptide had no effect on basal surface GABA A R expression (1.42 Ϯ 13.03% change from control; n ϭ 5; p Ͼ 0.1).…”
Section: Gabarap Is Central To Gaba a Receptor Insertion After Chem-ltdsupporting
confidence: 77%
See 2 more Smart Citations
“…Although a scrambled control peptide had no effect on the NMDA-mediated increase in GABA A R surface expression (48.9 Ϯ 9.18% increase from control; n ϭ 5; p Ͻ 0.05), when cells were pretreated with the GABARAP inhibitory peptide for 30 min, NMDA induced a significant decrease in GABA A R surface levels (Ϫ38.17 Ϯ 5.15%; n ϭ 5; p Ͻ 0.05). As reported previously (Kawaguchi and Hirano, 2007), disruption of the GABARAP-GABA A R interaction with the GABARAP inhibitory peptide had no effect on basal surface GABA A R expression (1.42 Ϯ 13.03% change from control; n ϭ 5; p Ͼ 0.1).…”
Section: Gabarap Is Central To Gaba a Receptor Insertion After Chem-ltdsupporting
confidence: 77%
“…Interestingly, it is not clear that expression of RP, although similar to the NMDAR-dependent potentiation described here, is caused by trafficking of GABA A Rs to synapses. In fact, Kawaguchi and Hirano (2007) reported no change in surface GABA A R expression after RP induction. It remains possible that GABARAP has multiple functions in regulating GABAergic signaling: through altered GABA A R function as seen in Purkinje neurons and through enhanced GABA A R numbers as we found in the hippocampus.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This “rebound potentiation” (RP) occurs through activation of voltage-gated Ca 2+ channels (VGCCs) resulting in a transient Ca 2+ influx and is dependent upon CamKII (Kano, Kano, Fukunaga, & Konnerth, 1996) and γ2 subunit association with GABARAP (Kawaguchi & Hirano, 2007). Further, RP can be suppressed by GABA type B receptor (GABA B R) activation through decreasing levels of PKA.…”
Section: Signaling Pathways That Modulate Gabaar Phosphorylationmentioning
confidence: 99%
“…Molecular regulation mechanisms of RP induction has been studied extensively [13], and it was revealed that interaction of GABA A receptor binding protein (GABARAP) and GABA A receptor is necessary for RP induction [16]. This result prompted us to examine physiological roles of RP using RP-deficient mice.…”
Section: Rp-deficient Micementioning
confidence: 99%